EIB Group Sustainability Report 2020 - European Investment Bank (European Investment Bank, 2021)
Supporting sustainable and inclusive growth is at the heart of the EIB Group's lending. The EIB Group 2020 Sustainability Report looks at the impact of our global activities and our own corporate responsibility efforts. The Sustainability report should be read in conjunction with its two annexes: the GRI and SASB disclosures.